Nucleotide-excision repair of DNA in cell-free extracts of the yeast Saccharomyces cerevisiae. - Wang, Z (1993)
A wide spectrum of DNA lesions are repaired by the nucleotide-excision repair (NER) pathway in both eukaryotic and prokaryotic cells. We have developed a cell-free system in Saccharomyces cerevisiae that supports NER. NER was monitored by measuring repair synthesis in DNA treated with cisplatin or with UV radiation. Repair synthesis in vitro was defective in extracts of rad1, rad2, and rad10 mutant cells, all of which have mutations in genes whose products are known to be required for NER in vivo. Additionally, repair synthesis was complemented by mixing different mutant extracts, or by adding purified Rad1 or Rad10 protein to rad1 or rad10 mutant extracts, respectively. The latter observation demonstrates that the Rad1 and Rad10 proteins directly participate in the biochemical pathway of NER. NER supported by nuclear extracts requires ATP and Mg2+ and is stimulated by polyethylene glycol and by small amounts of whole cell extract containing overexpressed Rad2 protein. The nuclear extracts also contain base-excision repair activity that is present at wild-type levels in rad mutant extracts. This cell-free system is expected to facilitate studies on the biochemical pathway of NER in S. cerevisiae.